A Comprehensive Review of Systemic Sclerosis: Diagnosis, Clinical Features and Management Strategies - Agnieszka Borowiec; Kinga Borowiec; Paulina Kwaśniewska; Julia Biernikiewicz; Milena Biernikiewicz; Anna Wilewska; Bartosz Pomirski; Agata Pomirska; Konstanty Alabrudziński; Miszela Kałachurska (Journal of Education, Health and Sport, 2025)
Introduction